The public dimension of Renato Constantino’s ‘historically-informed social criticism’ facets and critiques of his intellectual legacy, 1945-1978 - Guiang, Francisco Jayme Paolo A. (Philippine Social Sciences Review, 2020)
Access online through this link: https://journals.upd.edu.ph/index.php/pssr/article/view/8413/7354